When to consider retiring an athlete after sports-related concussion - Sedney, C. L.; Orphanos, J.; Bailes, J. E. (Clinics in Sports Medicine, 2011)
The pathophysiology of concussion may lead to a variety of both short- and long-term effects, which may lead to a decision to retire from contact sports. These effects follow a recognizable progression and may cause an athlete to opt out of play at any point along this progression. To elucidate the effect of concussion or mild traumatic brain injury and weigh in on a decision to retire, the treating physician needs to take into account the history, neurologic examination, brain imaging, and neuropsychological testing. In addition, myriad social factors surrounding play must be taken into consideration.